Estrogen receptor alpha and beta expression in normal endometrium and myometrium in premenopausal women - Wróbel, Andrzej; Adamiak, Aneta; J. Jakimiuk, Artur; Magoffin, Denis; A. Jakowicki, Jerzy; Haczyński, Józef; Bogusiewicz, Michał; Dziduch, Piotr; Tarkowski, Rafał (Menopause Review/Przegląd Menopauzalny, 2003)
Effects of estrogens are mediated by two types of estrogen receptor (ER-alfa and ER-beta). The responsiveness of target tissues to estrogens relies on the distribution of both receptor types as well as interactions between these two molecules. We aimed to evaluate the expression of ER-alpha and ER-beta genes in endometrium and myometrium in premenopausal women. Endometrium and myometrium samples were derived from 12 women subjected to surgery because of uterine leiomyomas. ER-alpha and ER-beta mRNAs were measured by quantitative assays based on reverse transcription (RT) of the mRNA and polymerase chain reaction (PCR) amplification of the cDNA. The expression of ER-alpha but not ER-beta was significantly higher in comparison to ER-beta in uterine myometrium. Interestingly, the expression of ER-alpha was higher in myometrium compared to endometrium, while the expression of ER-beta did not differ between these tissues. There were no differences in the ratio of ER-alpha/ER-beta expression between myometrium and endometrium. Our results indicate that differences in the expression of estrogen receptors between myometrium and endometrium are confined to receptor alpha.